Vital Signs Predict Rapid-Response Team Activation Within Twelve Hours of Emergency Department Admission - Walston, James M. (West J Emerg Med, 2016)
INTRODUCTION: Rapid-response teams (RRTs) are interdisciplinary groups created to rapidly assess and treat patients with unexpected clinical deterioration marked by decline in vital signs. Traditionally emergency department (ED) disposition is partially based on the patients’ vital signs (VS) at the time of hospital admission. We aimed to identify which patients will have RRT activation within 12 hours of admission based on their ED VS, and if their outcomes differed. METHODS: We conducted a case-control study of patients presenting from January 2009 to December 2012 to a tertiary ED who subsequently had RRT activations within 12 hours of admission (early RRT activations). The medical records of patients 18 years and older admitted to a non-intensive care unit (ICU) setting were reviewed to obtain VS at the time of ED arrival and departure, age, gender and diagnoses. Controls were matched 1:1 on age, gender, and diagnosis. We evaluated VS using cut points (lowest 10%, middle 80% and highest 10%) based on the distribution of VS for all patients. Our study adheres to the STROBE (Strengthening the Reporting of Observational Studies in Epidemiology) guidelines for reporting observational studies. RESULTS: A total of 948 patients were included (474 cases and 474 controls). Patients who had RRT activations were more likely to be tachycardic (odds ratio [OR] 2.02, 95% CI [1.25–3.27]), tachypneic (OR 2.92, 95% CI [1.73–4.92]), and had lower oxygen saturations (OR 2.25, 95% CI [1.42–3.56]) upon arrival to the ED. Patients who had RRT activations were more likely to be tachycardic at the time of disposition from the ED (OR 2.76, 95% CI [1.65–4.60]), more likely to have extremes of systolic blood pressure (BP) (OR 1.72, 95% CI [1.08–2.72] for low BP and OR 1.82, 95% CI [1.19–2.80] for high BP), higher respiratory rate (OR 4.15, 95% CI [2.44–7.07]) and lower oxygen saturation (OR 2.29, 95% CI [1.43–3.67]). Early RRT activation was associated with increased healthcare utilization and worse outcomes including increased rates of ICU admission within 72 hours (OR 38.49, 95%CI [19.03–77.87]), invasive interventions (OR 5.49, 95%CI [3.82–7.89]), mortality at 72 hours (OR 4.24, 95%CI [1.60–11.24]), and mortality at one month (OR 4.02, 95%CI [2.44–6.62]). CONCLUSION: After matching for age, gender and ED diagnosis, we found that patients with an abnormal heart rate, respiratory rate or oxygen saturation at the time of ED arrival or departure are more likely to trigger RRT activation within 12 hours of admission. Early RRT activation was associated with higher mortality at 72 hours and one month, increased rates of invasive intervention and ICU admission. Determining risk factors of early RRT activation is of clinical, operational, and financial importance, as improved medical decision-making regarding disposition would maximize allocation of resources while potentially limiting morbidity and mortality.